Search for disappearing tracks as a signature of new long-lived particles in proton-proton collisions at sv=13 TeV; Journal of High Energy Physics; Vol. 2018, iss. 8 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Baydali S. A. Sergey Anatolievich (2018, 2018)
Title screen